A decision-making framework for process plant maintenance. (2nd December 2009) - Ghosh, Devarun; Roy, Sandip
An optimal maintenance approach is a key support to industrial production in the contemporary process industry. This paper presents a Multiple-Criteria Decision Making (MCDM) methodology for selecting the optimal mix of maintenance approaches – Corrective Maintenance (CM), Time-Based Preventive Maintenance (TBPM) and Condition-Based Predictive Maintenance (CBPM) – for different equipment in a typical process plant. First, the criticality of each equipment from the point of view of maintenance is achieved by risk ranking them (based on the worst-case failure mode), thus prioritising them for maintenance interventions. Next, the MCDM methodology with a fuzzy adaptation of the Analytic Hierarchy Process (AHP) technique is applied to individual equipment. The criteria used as part of the MCDM model are safety, maintenance investment, business interruption loss and maintenance technique feasibility. Furthermore, this technique is embedded into a Goal Programming (GP) model to optimise multiple objectives such as risk reduction and cost minimisation that are subject to resource constraints. The present approach is an improvement over the contemporary approaches to decision making for maintenance management in that it integrates risk assessment with the GP-fuzzy AHP technique and is sufficiently generalised. The approach can aid in the formulation of a cost-effective maintenance approach for a plant. [Received 11 August 2008; Revised 31 December 2008; Revised 20 February 2009; Accepted 25 February 2009]